Pengaruh Make a Match Terhadap Kemampuan Menulis Teks Descriptive Siswa - Nina Nurbaidah (Institut Pendidikan Tapanuli Selatan, 2017)
The aim of this research is to know whether the effect of using Make a Match on students’ writing descriptive text ability gives a better result at the first grade students of STKIP Tapanuli Selatan in 2014/2015 Academic Year. The writer uses an experimental method. The population is the first grade students of STKIP Tapanuli Selatan, which consisted of 60 students. Two classes, they are I-A and I-B are taken as two groups of sample by total sampling. The whole amount samples is 60 students. The data are collected by using 2 items test as an instrument. The writer uses statistic processes in analyzing data. They are descriptive analysis by using the formula of “t-test”. After calculating the data, it is found that the result of writing ability on descriptive text taught by using Make a Match method is categorized “good”. While the students’ writing ability on descriptive text taught by using Group Investigation method as a conventional teaching method is categorized “enough”. The result of the analyzed data shows that 2,34 > 1,67 or t-test is greater than t-table. so, the hypothesis is accepted. It means, there is a significant effect on Student’s Writing Descriptive Text Ability Taught By Using Make A Match Method at the first Grade Students of STKIP Tapanuli Selatan. Keywords: Make A Match and Group Investgation Methods, Writing Descriptive Text.